An 16-bit fixed-point square root operation using VHDL - Ahmad Juzaili, Alias (2008)
Digital design is a part of human life nowadays; we cannot deny its existence in our life. The simple example would be our computer. Behind its functionality in doing its jobs and task, there is a complex design of digital system that play the role part of executing the operation so that our computer can perform its task when given one. On the other hand, square root is one of an important part in scientific calculation, computer graphic applications. Hence, square root is one of the operation that important for computer to performs its task. The programming languages used is VHDL (Very High Speed Integrated Circuit Hardware Description Language). The software used is ISE 10.1 that were specially made to interface with Xilinx development board. Through successfully creates it, simulation can be done and verify the system with it functionality. Hence, a digital system that operates as fixed –point square root is created.